The Role of German Diaspora in Russian-German Relations - P. I. Kasatkin; V. S. Kurske; I. A. Valiev (Vestnik MGIMO-Universiteta)
German Diaspora played and plays significant role in Russian-German relations. It is very important for cooperation in humanitarian sphere, education and culture. Key actors are Germany as «the external homeland», German diaspora and Russia as «the accommodation country». In the activity concerning the Russian Germans all three parties are guided by various principles and purposes that sometimes leads to tensions and the conflicts. But as a whole we have to note that the Russian Germans became a constructive link between Germany and Russia.